Vulval pain: vulvodynia. (May 2022) - Taghinejadi, Neda; Lord, Emily; Edwards, Anne
Abstract: Vulvodynia is a heterogenous gynaecological condition that can have a significant impact on the physical and psychological well-being of affected women. It should be considered within the differential diagnosis in a number of gynaecological presentations, including superficial dyspareunia, apparent persistent/recurrent candidiasis and chronic vulval symptoms such as discomfort and itch. Although vulvodynia is widely considered to be an idiopathic pain syndrome, there is a growing body of research into a complex array of factors thought to play a role in its pathogenesis. There is no 'one-size-fits-all' approach to treatment; successful management often relies upon a multimodal and multidisciplinary approach. Despite its high prevalence, vulvodynia remains a poorly recognized condition and women often experience barriers in accessing diagnosis and treatment. Promoting increased awareness of vulvodynia among clinicians and the wider public is therefore an important endeavour.